Authentication Mechanisms for Mobile Learning Applications: a Usability Study - Hean Yong, Kang; Katuk, Norliza; Haryani Zakaria, Nur (International Journal of Engineering and Technology, 2018)
Authentication is a security component that maintains user access to applications. It has been the primary reason for users to create usernames and passwords before they can use applications. In creating usernames and passwords; users are required to fill in their personal information in which it is a time-consuming process. Additionally, it also increases the number of usernames and passwords that users need to remember which leads to password fatigue. Social login is a way to address this problem. With the benefits that social login could offer, this study aims to study the usability of social login for mobile learning. Further, the user’s preference towards authentication mechanisms used for mobile learning applications was identified. An experimental study was conducted using a mobile learning application named LANGKAWI ISLANDS. Forty participants participated in this study on a voluntary basis and used the traditional and social login on LANGKAWI ISLANDS. The time taken by the participants to sign up the application using both mechanisms was recorded. The usability of the authentication mechanisms was evaluated using a self-report questionnaire. Then, the participants stated their preference for the authentication mechanisms. The results suggest that the social login is more usable than the traditional authentication mechanism. Further, the users’ signup process for LANGKAWI ISLANDS is much faster using social login and has been the primary users’ preference for mobile learning authentication mechanism.
Keywords: User authentication; social network; social network login; social login; user credentials.